2014
DOI: 10.3233/ch-141904
|View full text |Cite
|
Sign up to set email alerts
|

The role of VTIQ as a new tissue strain analytics measurement technique in testicular lesions

Abstract: PURPOSE: Virtual touch tissue imaging quantification (VTIQ) is a newly developed technique for the sonographic quantification of tissue elasticity. It has been used in the assessment of breast lesions. The purpose of this study was to determine the diagnostic performance of VTIQ in indeterminate testicular lesions. METHODS: Twenty patients with known testicular pathology underwent conventional B-mode sonography with additional VTIQ of the testicular lesions using a Siemens Acuson S2000™ and S3000™ (Siemens Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…To date, only 1 study reported the application of VTIQ for evaluating thyroid nodules, 22 although VTIQ has been shown to be useful and reproducible in accessing breast lesions and other organs. 19,20,32,33 In this study, the SWV parameters in malignant nodules were all higher than those in benign nodules, and the SWV mean showed the highest AUC value among them, with a cutoff value of 2.90 m/s. By comparison, in a previous study, Azizi et al 22 reported that VTIQ showed an AUC of 0.78 with a cutoff value of 3.54 m/s.…”
Section: Discussionmentioning
confidence: 51%
“…To date, only 1 study reported the application of VTIQ for evaluating thyroid nodules, 22 although VTIQ has been shown to be useful and reproducible in accessing breast lesions and other organs. 19,20,32,33 In this study, the SWV parameters in malignant nodules were all higher than those in benign nodules, and the SWV mean showed the highest AUC value among them, with a cutoff value of 2.90 m/s. By comparison, in a previous study, Azizi et al 22 reported that VTIQ showed an AUC of 0.78 with a cutoff value of 3.54 m/s.…”
Section: Discussionmentioning
confidence: 51%
“…Trottmann et al. ( 12 ) showed a mean of 1.17 m/s in a normal testicle, and D’Anastasi et al. showed a range of 0.62–1.01 m/s in healthy volunteers ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the observed mean velocity in men with testicular cancer was 2.10 m/s, but we found a calculated predicted mean of 1.92 m/s. Trottmann et al investigated seven patients with germ cell tumors and five with seminoma using virtual touch imaging quantification (VTIQ), and the results were a mean shear wave velocity of 1.94 m/s in germ cell tumors and 2.42 m/s in seminoma 22 . Macron et al investigated the testes of 20 healthy patients using SWE and found a mean SWE of 0.81 m/s and a mean VTIQ of 1.07 m/s 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Elastography is used in various organs 7 9 10 11 and also in the testicles for investigating testicular torsion 12 13 , testicular cancer 14 15 infarction 16 17 , epidermoid cysts 18 , undescended testes 19 , infertile men 20 , hemodialysis patients 21 , testicular microlithiasis, and other lesions 22 23 24 . It can be challenging to distinguish hard tumors in soft tissue using only B-mode ultrasound.…”
Section: Introductionmentioning
confidence: 99%